Assessment of yield losses due to Mungbean yellow mosaic India virus and evaluation of mungbean genotypes for resistance in South-West Punjab - K.S. BRAR, M.S. YADAV* and (Indian Phytopathology, 2010)
The yield attributes were assessed on mungbean variety SML 134 by maintaining five grade of mungbean yellow mosaic virus (MYMV) infection (1-9) under natural epiphytotic conditions of Bathinda (Punjab) during 2004 and 2005. Result revealed that with the increased levels of MYMV severity, the corresponding yield attributes decreased significantly. Per plant reduction in seed yield varied from 22.3 to 61.7% under resistant (grade 1) to highly susceptible (grade 9) in comparison to healthy control. On an average 43.6% reduction in seed yield were assessed on moderate level of susceptibility (grade 5) over healthy control. Out of 40 genotypes evaluated against MYMV, two genotypes namely NM 57 and NM 94 were found resistant and four genotypes (PBM 118, PBM 121, PBM 123 and A 3) were found moderately resistant. Resistant and moderately resistantgenotypes possessing better phenotypic characters and yield attributes identified in these studies could be utilized in mungbean improvement programme.